WATER QUALITY AND PLANKTON COMPOSITION FOR FRESHWATER FISH FARMING IN THE WATERS OF PARIT KELADI VILLAGE, KUBU RAYA REGENCY, WEST KALIMANTAN - Pratomo, M. Farhan Budi; Hasan, Hastiadi; Lestari, Tuti Puji (Asian Journal of Aquatic Sciences, 2024)
Waters in Parit Keladi Village have potential fish resources that cannot be developed due to household and agricultural waste contamination. This study aims to analyze water quality and plankton composition in the waters of Parit Keladi Village for freshwater fish farming. The study used a survey method in three locations, namely waters upstream, around residential areas, and downstream. Water quality parameters analyzed were temperature, depth, brightness, salinity, IDS, DO, BOD, COD, ammonia, nitrite, and nitrate. Plankton species, density, and biological index were analyzed. The results showed that the three locations' temperature, salinity, brightness, IDS, DO, COD, ammonia, nitrate, and nitrite met the national water quality standards for freshwater fish farming. However, BOD and depth values still did not meet the standard values. Planktons found consisted of 29 phytoplankton species and I zooplankton species with a total density of 9,350x103 cell/mL at location I, 9,540x103 cell/mL at location II, and 8,300x103 cell/mL at location III. The level of diversity was low, with the dominance of Chlorella vulgaris and Chroococcus species. It is concluded that water quality and plankton composition in the waters of Parit Keladi Village still need to be managed to develop freshwater fish farming